Nasionalisme Islam: Pandangan Redaksi Surat Kabar Neratja, 1917-1924‎ - Emalia, Imas; Mahrani, Fahreiza (UIN SIber Syekh Nurjati Cirebon, 2025)
This research focuses on the views of the Neratja newspaper in responding to the early days of nationalism in the Netherlands East Indies during 1917-1924. Using the framing analysis theory derived from mass communication, this study tries to answer how the embodiment of the ideology of the Neratja newspaper in reporting the initial process of nationalism in the Netherlands East Indies. The result of the analysis found from this discussion is that the Neratja newspaper is affiliated with the central figures of the Islamic Movement who are able to frame the situation in the Indies by putting forward the bumiputera idea of the narrative Islam is more depressed, oppressed and persecuted.. This daily newspaper offers Islamic thought as the basis of spiritual power in a nationalistic style. Coming out of the initial publishing concept, The ideal of creating a neutral press in Neratja was not realized because of his firmness and courage to reject Kaoem Sana (Capitalist) to become a friend of Kaoem Sini (Indigenous). The conclusion of the findings shows that Neratja as one of the largest indigenous newspapers in the Netherlands East Indies has a strategic position and has a great influence in voicing the rights and obligations of the natives, resisting the threat of communism, and teaching love for the homeland based on faith.Keywords: Neratja, Indigenous Press, Early Nationalism, Islamic Ideology, Framing.